2002
DOI: 10.1074/jbc.m112109200
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein E4 Potentiates Amyloid β Peptide-induced Lysosomal Leakage and Apoptosis in Neuronal Cells

Abstract: We assessed the isoform-specific effects of apolipoprotein (apo) E on the response of Neuro-2a cells to the amyloid ␤ peptide (A␤1-42). As determined by the intracellular staining pattern and the release of ␤-hexosaminidase into the cytosol, apoE4-transfected cells treated with aggregated A␤1-42 showed a greater tendency toward lysosomal leakage than neo-or apoE3-transfected cells. A␤1-42 caused significantly greater cell death and more than 2-fold greater DNA fragmentation in apoE4-secreting than in apoE3-sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
150
0
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 166 publications
(159 citation statements)
references
References 110 publications
(70 reference statements)
7
150
0
2
Order By: Relevance
“…In cultured Neuro-2a cells, we showed that apoE4 enhances A␤-induced lysosomal leakage and apoptotic cell death to a much greater extent (2-to 4-fold) than apoE3 (74,127).…”
Section: Apoe4 Potentiation Of A␤-induced Lysosomal Leakage and Apoptmentioning
confidence: 90%
“…In cultured Neuro-2a cells, we showed that apoE4 enhances A␤-induced lysosomal leakage and apoptotic cell death to a much greater extent (2-to 4-fold) than apoE3 (74,127).…”
Section: Apoe4 Potentiation Of A␤-induced Lysosomal Leakage and Apoptmentioning
confidence: 90%
“…Current knowledge of the differential functioning among the ApoE isoforms, either in lipid metabolism or neuronal protection, does not readily provide a rationale for the observed protective role of E4 against AMD development [Nathan et al, 1994;Ji et al, 2002;Laws et al, 2003]. ApoE is expressed in photoreceptor outer-segments, the retinal ganglion layer, and both layers of Bruch's membrane.…”
Section: Discussionmentioning
confidence: 99%
“…Incubation with wild-type ApoE E3 or variant ApoE E4-enriched 3-VLDL results in differential cellular accumulation [Ji et al, 1998;Laws et al, 2003]. A two-to threefold increase in the accumulation of ApoE E3 over ApoE E4 has been observed in various cell types [Ji et al, 2002]. If mechanisms for proper clearance in the retina and Bruch's membrane are not in place, this accumulation may serve as a pathogenic basis for disease development [Ambati et al, 2003;Tuo et al, 2004b].…”
Section: Discussionmentioning
confidence: 99%
“…They include modulation of the deposition and clearance of A␤ peptides and the formation of plaques (15)(16)(17)(18)(19)(20)(21), impairment of the antioxidative defense system (22), dysregulation of neuronal signaling pathways (23), altered phosphorylation of tau and NFT formation (24 -29), depletion of cytosolic androgen receptor levels in the brain (30,31), potentiation of A␤-induced lysosomal leakage and apoptosis in neuronal cells (32), and promotion of endosomal abnormalities linked to A␤ overproduction (33)(34)(35). However, the mechanisms of these apoE4-mediated detrimental effects are largely unknown, and it is not known which are the primary effects and which are subsequent or downstream effects.…”
mentioning
confidence: 99%